Evaluation of the sperm separability of blanc-blue-belge bull by swim-up method and in vitro embryo production with hybrid Zebu bovine oocyte in Vietnam - Huu Duc, Nguyen; Thu Giang, Pham; Binh Nguyen, Tran Thi; Dai Phong, Bui (Vietnam Journal of Biotechnology, 2020)
The objective of this study was to determine the right conditions for the separation of Blanc-Blue-Belge bovine sperm (BBB) by swim-up mothed; determine the maturity of hybrid Zebu bovine eggs; and culture of embryos after in vitro fertilization. After 60-80 minutes of swim-up in CAP-05, BBB bovine sperms were healthy, straight movement and separated with a concentration of 106 sperm/ml. Hybrid Zebu bovine eggs developed and matured in the maturation medium with the basic medium TCM-199 supplemented with 10% calf serum, FSH (0.75 µg / ml), LH (0.15 µg / ml) and Estradiol (2.5 µg / ml), the results showed that the IVM-08 medium had significantly higher maturation rates than IVM-03, the proportion of mature eggs reached 71,11% compared to 51.69%, respectively (P <0.01). In vitro fertilization of hybrid Zebu bovine egg in IVF-08 medium. In vitro fertilized embryos (BBB x hybrid Zebu) developed from bovine sperms separated by the swim-up method achieved a better rate of morula-blastocysts in IVC-09 than IVC-06 medium, 21.68% compared to 8.56%, respectively (P <0.01). The conclusion was that the suitable conditions for BBB bovine sperm separation and in vitro embryo production (BBB x hybrid Zebu) were determined. This is the premise to create bovine semen, BBB bovine embryos with defined gender.